Understanding pathways to social inequalities in childhood unintentional injuries: findings from the UK millennium cohort study - M. Campbell; E. T. C. Lai; A. Pearce; E. Orton; D. Kendrick; S. Wickham; D. C. Taylor-Robinson (BMC, 2019)
Abstract Background Childhood unintentional injuries (UI) are common but continue to happen more often to children living in less advantaged socioeconomic circumstances (SEC). Our aim was to explore how early life factors mediate the association between SEC and UIs, using the UK Millennium Cohort Study. Methods We calculated risk ratios (RR) and 95% confidence intervals (95%CI) for parental report of UI occurring between age 3 and 5 years, using Poisson regression according to family income as a measure of SEC. We explored potentially mediating pathways by controlling associations between SEC and UI for groups of early life risks in three domains: factors that may influence environmental safety, supervision and the MCS child's abilities and behaviours. Results Twenty eight percent of children had a UI from 3 to 5 years old. Children from the lowest income quintile were more likely to be injured compared to those from the highest (RR 1.20 95%CI 1.05, 1.37). Sequentially controlling for early life factors that may influence environmental safety (RR 1.19 95%CI 1.02, 1.38), then supervision (RR 1.18, 95%CI 1.02, 1.36), and finally adding child's behaviour and abilities (RR 1.15, 95%CI 1.00, 1.34) into the model reduced the RR by 5, 10 and 25% respectively. Conclusions Addressing factors that may influence environmental safety and supervision, and the child's abilities and behaviours only partly explains the increased UI risk between the highest and lowest income quintiles. Further research is required to explore factors mediating associations between SEC and specific mechanisms and types of injuries.